Hypertension awareness, treatment and control in Africa: a systematic review - Kayima, James; Wanyenze, Rhoda K; Katamba, Achilles; Leontsini, Elli; Nuwaha, Fred (BMC cardiovascular disorders, 2013)
Background Inadequate diagnosis and suboptimal control of hypertension is a major driver of cardiovascular morbidity and mortality in Africa. Understanding the levels of awareness, treatment and control of hypertension and the associated factors has important implications for hypertension control efforts. Methods The PubMed database was searched for original articles related to awareness, treatment and control of hypertension in Africa published between 1993 and 2013. The key search terms were: Africa, awareness, treatment, control, and hypertension. Exploration of bibliographies cited in the identified articles was done to provide further studies. Full texts of the articles were obtained from various internet sources and individual authors. A data extraction sheet was used to collect this information. Results Thirty eight studies drawn from 23 African countries from all regions of the continent met the inclusion criteria. The levels of awareness, treatment and control varied widely from country to country. Rural populations had lower levels of awareness than urban areas. North African countries had the highest levels of treatment in the continent. There was generally poor control of hypertension across the region even among subjects that were aware of their status and those that were treated. On the whole, the women had a better control status than the men. Conclusion There are low levels of awareness and treatment of hypertension and even lower levels of control. Tailored research is required to uncover specific reasons behind these low levels of awareness and treatment, and especially control, in order to inform policy formulation for the improvement of outcomes of hypertensive patients in Africa.